Albert Cohen Dissonant Voices - Abecassis, Jack I. (Johns Hopkins University Press, 2004)
Honorable Mention winner in the Modern Language Association's Aldo and Jeanne Scaglione Prize competition for French and Francophone Literary StudiesA major figure in twentieth-century letters, Albert Cohen (1895-1981) left a paradoxical legacy. His heavily autobiographical, strikingly literary, and polyphonic novels and lyrical essays are widely read by a devout public in France, yet have been largely ignored by academia. A self-consciously Jewish writer and activist, Cohen remained nevertheless ambivalent about Judaism. His self-affirmation as a Jew in juxtaposition with his satirical use of anti-Semitic stereotypes still provokes unease in both republican France and institutional Judaism.In Albert Cohen: Dissonant Voices, the first English-language study of this profound and profoundly misunderstood writer, Jack I. Abecassis traces the recurrent themes of Cohen's works. He reveals the dissonant fractures marking Cohen as a modernist, and analyzes the resistance to his work as a symptom of the will not to understand Cohen's main theme-"the catastrophe of being Jewish."For Abecassis, Cohen's diverse oeuvre forms a single "roman fleuve" exploring this perturbing theme through fragmentation and grotesquerie, fantasies and nightmares, the veiling and unveiling of the unspeakable.Abecassis argues that Cohen should not be read exclusively through the prism of European literature (Stendhal, Tolstoy, Proust), but rather as the retelling-inverting and ultimately exhausting, in the form of submerged plots-of the Biblical romances of Joseph and Esther. The romance of the charismatic Court Jew and its performance correlative, the carnival of Purim, generate the logic of Cohen's acute psychological ambivalence, historical consciousness and carnal sensuality-themes which link this modernist author to Genesis as well as to the literary practices of Sephardic crypto-Jews. Abecassis argues that Cohen's best-known work, Belle du Seigneur (1968), besides being an obvious tale of obsessive love and dissolution, is foremost a tale of political intrigue involving Solal, the meteoric-rising Jew in the League of Nations during the period of Appeasement (1936), and his ultimate self-destruction. Providing close readings and imaginative analyses of the entire literary output of one of twentieth-century France's most important Jewish writers, Abecassis presents here a major work of literary scholarship, as well as a broader study of the reception and influence of Jewish thought in French literature and philosophy.